Assessing teachers’ knowledge of school based assessment practices in Nigeria secondary schools - Temitope Babatimehin; Oluwaseyi Aina Gbolade Opesemowo; Isaac Bamikole Ogunsakin; Temitope Sarah Ogungbaigbe (Discover Education)
Abstract The study determined teachers' knowledge of key issues such as classroom assessment, teaching process and assessment procedure in school-based assessment (SBA). It determined the level of SBA implementation in the classroom environment, teaching processes and assessment procedures in Ondo State secondary schools. These were to improve assessment processes and practices in secondary schools in the State. A mixed-method research design was employed for the study. The population comprised principals and teachers of secondary schools in Ondo State. The sample consisted of 600 schoolteachers and 30 principals. Thirty secondary schools were selected by purposive and Stratified Random sampling from three local government areas (LGAs). For the quantitative aspect, data were collected using Teachers’ Knowledge of Key Issues in SBA practice (TKSBA) and analyzed using descriptive and inferential statistics. While qualitative data were thematically analyzed. Results showed that 62.2% of the male teachers and 65.6% of female teachers had low knowledge of key issues of SBA practice. The study concluded that systemic issues and the poor implementation of SBA practice in Ondo State secondary schools led to teachers’ inadequate knowledge of key issues in SBA practice.